2017
DOI: 10.1111/nep.13015
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for newer biomarkers in chronic kidney disease‐mineral and bone disorder management?

Abstract: ABSTRACT:The current management of Chronic Kidney Disease-Mineral Bone Disorder (CKD-MBD) relies largely on clinical judgement and assessment of biochemical parameters including serum calcium, phosphate and intact parathyroid hormone concentrations. In the past two decades, there has been a leap in the understanding of the pathophysiology of CKD-MBD, leading to the discovery of novel biomarkers. The potential utility of these markers in this clinical setting is an area of intense investigation. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Although the results of relations between circulating klotho levels and outcomes of CKD are contradictory, three commonly used commercial immunoassay products for measuring soluble klotho-- are available from IBL (IBL International GmbH, Hamburg, Germany), Cusabio (Cusabio Biotech, Wuhan, China), and USCN (USCN Life Science Inc., Wuhan, China) [ 159 ]. Only the IBL kit provides information on epitope specificity [ 159 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of relations between circulating klotho levels and outcomes of CKD are contradictory, three commonly used commercial immunoassay products for measuring soluble klotho-- are available from IBL (IBL International GmbH, Hamburg, Germany), Cusabio (Cusabio Biotech, Wuhan, China), and USCN (USCN Life Science Inc., Wuhan, China) [ 159 ]. Only the IBL kit provides information on epitope specificity [ 159 ].…”
Section: Main Textmentioning
confidence: 99%
“…Although the results of relations between circulating klotho levels and outcomes of CKD are contradictory, three commonly used commercial immunoassay products for measuring soluble klotho-- are available from IBL (IBL International GmbH, Hamburg, Germany), Cusabio (Cusabio Biotech, Wuhan, China), and USCN (USCN Life Science Inc., Wuhan, China) [ 159 ]. Only the IBL kit provides information on epitope specificity [ 159 ]. However, researchers have found that these assays exhibited poor performance, including a lack of unit standardization in readouts, and the assays have to be improved to produce accurate results before they can provide reliable conclusions [ 160 ].…”
Section: Main Textmentioning
confidence: 99%
“…3,4 Therefore, the utility in identifying additional biomarkers to better evaluate, diagnose, and treat patients with CKD5-HD with MBD is appealing. [8][9][10][11] Osteopontin (OPN) is a glycol-phosphoprotein found in bone, acute and chronic inflammatory cells, smooth muscle, epithelial, and endothelial cells, neurons, and fetal renal tissue and is expressed in the thick ascending limb of the loop of Henle. 12,13 Some of its functions include increasing macrophage and T-cell counts, perpetuation of inflammation, wound healing, tumor development and progression, roles in diabetes, and possible roles in the regulation of nephrolithiasis and nephrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, the utility in identifying additional biomarkers to better evaluate, diagnose, and treat patients with CKD5-HD with MBD is appealing. 8 -11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation